Modern information technology in the system of accounting and analytical support of economic security of an enterprise - Shmatkovska, Tetiana O.; Шматковська, Тетяна Олександрівна (Національний університет "Львівська політехніка", 2017)
Визначено значення сучасних інформаційних технологій в формуванні обліково-аналітичного забезпечення в системі економічної безпеки підприємства. Автором окреслено основні проблеми становленні і розвитку обліково-аналітичного забезпечення у вітчизняному бізнес-середовищі. В роботі обґрунтовано, що автоматизоване облікове та аналітичне забезпечення є складовою частиною економічної безпеки підприємства і утворює комплексну інформаційну систему, яка поєднує в собі методи і технології бухгалтерського обліку, аналізу та процесу прийняття управлінських рішень щодо подолання внутрішніх і зовнішніх загроз та забезпечення сталого розвитку підприємства. Economic security has a sign of management and it is discrete in nature. This requires the development of appropriate theoretical and methodological apparatus designed to provide a favorable environment for the formation of accounting and analytical information, adequate management objectives that will contribute to effective management decisions. Despite the value of scientific contributions of the scientists, there are still a number of unsolved theoretical and practical problems related to non-compliance organization providing accounting and analytical purposes of economic security. The aim of the paper is to define the content and structure of accounting and analytical support in the system of economic security, its conformity to modern conditions of business environment. The mechanism of accounting and analytical software provides the collection of data , its methods of synthesis and analysis, and the technique of providing the direct users an assess to the level of economic security of their own company or their partners and / or competitors whose activities may affect the security. So, we can form the main directions of implementation of accounting and analytical support in the system of economic security: - diagnostics of financial and economic situation of the company in order to prevent its financial risks insolvency, bankruptcy; - assessment of economic security and their own company, the reliability of potential partners of the company; - evaluation of the safety and determine the strategy of market potential and actual competitors; preservation and enhancement of the potential resource of the company, its rational and effective use; - management decision-making regarding the advisability of activity considering the identified threats and hazards; - providing the most completed informational system of economic security as a whole, its individual functional units; - promote the harmonization of interests of the company as a whole (as a legal entity and individual employees (as individuals)) to minimize internal threats etc. Considering this, the principal organization of accounting and analytical software is the one, which refers to a set of tools, methods and techniques to streamline and optimize the accounting and analytical information. It is the awareness of stakeholders and people taking business decisions that is important factor in increasing the economic viability of the business, its efficiency and protection from exposure to internal and external threats. In the system of economic security arises the question of formation of complete and accurate information tailored to specific tasks and decision-making businesses. We believe that the structure of accounting and analytical economic security business is complex and extensive and is not limited to those structural components that are proposed by the author. Our studies provide an opportunity to formulate a series of generalized provisions that reveal the content of economic categories "Accounting and analytical support" and clarify its role as a significant factor in ensuring the economic security of the system entity. First, accounting and analytical information is an economic model of the relationship between the system of economic security, information resources, what it is, and the informational process in the middle of the company. Second, accounting and analytical information in the system of economic security can be characterized by different combinations of inherent properties (e.g., relevance, appropriateness, usefulness, etc.). A set of various properties is determined by the specific goals of obtaining information and its use. Thirdly, accounting and analytical information in the system of economic security is formed in the process of implementing three management functions: accounting, analysis and synthesis. However, the findings allow to state that in modern development theory and methodology of accounting and analytical support the functioning of economic security has a number of issues concerning the diagnosis of economic security, the use of innovative tools that require further consideration. Key words: information technology; accounting and analytical support; economic security; automation; the automated accounting and analytical support.
Сучасні інформаційні технології в системі обліково-аналітичного забезпечення економічної безпеки підприємства
Keywords: інформаційні технології; обліково-аналітичне забезпечення; економічна безпека; автоматизація; автоматизоване обліково-аналітичне забезпечення; information technology; accounting and analytical support; economic security; automation; the automated accounting and analytical support